Pelatihan Penggunaan Google Classroom Bagi Orang Tua Siswa SDK Mardiwiyata 2 Malang - Vinno Christmantara; Fernando Jason Sugiharto (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
SDK Mardiwiyata II Malang like nowadays education institutions has shared the same difficulties using Google Classroom as a learning platform during the pandemic. Some problem identified as follows: parents have confusion on 1) joining the class either using a code or an invitation from the teachers 2) reply the thread announcement 3) accessing the materials 4) submitting the assignments and quizzes 5) communicating using a Google Meet. The results of these training activities indicated that most of the parents can understand the basic features of Google Classroom. These results were obtained from the Google Form of the post-training questionnaire that been responded from 151 respondents.